MAKNA RUANG PADA TANEAN LANJANG DI MADURA - Tulistyantoro, Lintu (Dimensi Interior, 2005)
The understanding of the meaning of space between the traditional society and the modern society posses a very significant difference. The modern consideration of emphasizing on function is not always revelent if applied to determining the meaning of space according to the traditional society. The expression of space in a traditional Madura House%2C or generally mentioned as tanean lanjang%2C is one example of a cultural product that was created on the basis of the meaning that corresponds to foundation of the thoughts of its society. This is highly influenced by the presence and the lifestyle of its society. The meaning of space is not only based by merely aesthetic and visual understanding. Instead%2C the meaning of space is more frequently based on the deepest essence of what lies in the genuine mind of the its society. Because of that%2C visual expression is principally a reflection of the basic value of the nature or genuine identity of its society. Abstract in Bahasa Indonesia : Pemahaman akan makna ruang antara masyarakat tradisional dan masyarakat modern memiliki perbedaan yang sangat mencolok. Pertimbangan fungsional oleh masyarakat modern tidak selalu benar bila dipakai untuk mengkaji makna ruang oleh masyarakat tradisional. Ekspresi ruang pada susunan rumah tradisional Madura%2C atau yang lazim disebut tanean lanjang%2C adalah salah satu contoh hasil olah budaya yang lebih didasarkan kepada makna yang mendasari pola pemikiran masyarakatnya. Hal tersebut sangat dipengaruhi oleh keberadaan dan cara hidup masyarakatnya. Makna ruang tidak hanya didasari oleh pengertian estetis dan visual semata. Pemaknaan lebih didasarkan kepada esensi terdalam dari apa yang ada dalam alam pemikiran masyarakatnya. Karena itulah ekspresi visual adalah cerminan nilai dasar dari jati diri masyarakatnya. meaning%2C space%2C tanean lanjang.